Generation of Multishell Magnetic Hybrid Nanoparticles by Encapsulation of Genetically Engineered and Fluorescent Bacterial Magnetosomes with ZnO and SiO2. Issue 33 (8th June 2015) - Borg, Sarah; Rothenstein, Dirk; Bill, Joachim; Schüler, Dirk
<x xml:space="preserve">Abstract</x> Magnetic nanoparticles (MNPs) have great potential in biomedical applications, but the chemical synthesis of size‐controlled and functionalized core–shell MNPs remain challenging. Magnetosomes produced by the magnetotactic bacterium Magnetospirillum gryphiswaldense are naturally uniform and chemically pure magnetite MNPs with superior magnetic characteristics. Here, additional functionalities are made possible by the incorporation of biomolecules on the magnetosome surface; the magnetosome system is then chemically encapsulated with an inorganic coating. The novel multishell nanoparticles consist of the magnetosome core—which includes the magnetite crystal, the magnetosome membrane, and additional moieties, such as the enhanced green fluorescent protein (EGFP) and peptides—and an outer shell, comprising either silica or zinc oxide. Coating the functionalized magnetosomes with silica improves their colloidal stability and preserves the EGFP fluorescence in the presence of proteases and detergents. In addition, the surface charge of magnetosomes can be adjusted by varying the coating. This method will be useful for the versatile generation of new, multifunctional, multishell, and magnetic hybrid nanomaterials with potential applications in various biotechnological fields.